Archetype of the shadow in the novel "Death" by B. Antonenko-Davydovych (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article writer analyzes the novel “Deth”of B. Antonenko-Davidovich, the Ukrainian  writer of XX century, from the position of representation of the archetype Shadow. This allows to note down the novel into the literary context and at the same time to understand the primary source of national and individual consciousness. Archetypal analysis work contributes to the deverbalization of content and  outlining the author's intentions more clearly.
Keywords: archetype; national consciousness; author’s intention